Легкоатлетичний біг як засіб оздоровлення різних верств населення - Ячнюк, Максим; Iachniuk, Ячнюк, Iryna, Ирина; Ячнюк, Юрий (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка, 2019)
Розвиток ідей здорового способу життя вимагає визначення основних його компонентів. Більшість науковців і практиків вважа-ють, що здоровий спосіб життя включає трудову діяльність, опти-мальний руховий режим, відмову від шкідливих звичок, особисту гігієну, загартування, раціональне харчування. Основою методики формування здорового способу життя є оптимальна рухова актив-ність. Рухова активність людини, фізичні вправи є незамінними засобами профілактики захворювань, важливими факторами зміц-нення здоров’я людини і підтримки його працездатності. До зви-чайної рухової активності, за визначенням Всесвітньої організації охорони здоров’я, відносять види рухів, спрямовані на задоволення природних потреб людини (сон, особиста гігієна, приймання їжі, зу-силля, витрачені на її приготування, придбання продуктів), а також навчальну та виробничу діяльність, а спеціально організована ру-хова активність включає різні форми занять фізичними вправами. Різноманітність фізичних вправ, точність регулювання навантажень, відносна простота обладнання місць занять роблять легку атлетику масовим видом спорту, доступним людям будь-якого віку.
Athletics run how a type of sanitation different population groups
The development of healthy lifestyle requires the identification of its main components. Most scholars and practitioners believe that a healthy lifestyle includes work, optimal motor mode, refuse from bad habits, personal hygiene, hardening, rational feeding. The optimal motor activity is basis of the method of forming a healthy lifestyle. Human’s motor activity are indispensable means of preventing diseases, important factors of strengthening the health of a person and maintaining his ability to work. By the usual motor activity, according to the definition of the World Health Organization, include types of movements aimed at satisfying the natural human needs. These include dream, personal hygiene, food intake, efforts spent on its preparation, purchase of products. Also related with training and production activities, and specially organized motor activity includes various forms of physical exercises. A variety of physical exercises precision adjustment activity relative ease of equipment for places of work make athletic a mass sport, accessible to people of all ages. The important thing in mass exercises is not the result, but the pleasure which receives person from the process of outside aerobic exercise. This helps to abstract from the usual worries, as well as the health effects, maintaining a high level of physical condition, because in the exercise takes involved most muscles of the body. Wellness runs contributes to positive changes in the muscles, which are to increase their mechanical efficiency, capillization, increase the size of fibers, increase the enzymatic activity in mitochondria. The main motives for doing well-doing runs are disease prevention, increased work capacity, satisfaction with the process, knowledge of the capabilities of your body. Regular wellness runs are good for health and can be recommended for improving the functional state, preventing diseases and improving the body’s resistance to adverse environmental factors.
Keywords: легка атлетика, біг, ходьба, оздоровча діяльність; athletics, running, walking, recreational activities